Measures of insulin sensitivity, leptin, and adiponectin concentrations in cats in diabetic remission compared to healthy control cats - Gottlieb, Susan; Rand, Jacquie S.; Ishioka, Katsumi; Dias, Daniel A.; Boughton, Berin A.; Roessner, Ute; Ramadan, Ziad; Anderson, Stephen T. (Frontiers in Veterinary Science, 2022)
Objectives: Firstly, to compare differences in insulin, adiponectin, leptin, and measures of insulin sensitivity between diabetic cats in remission and healthy control cats, and determine whether these are predictors of diabetic relapse. Secondly to determine if these hormones are associated with serum metabolites known to differ between groups. Thirdly, if any of the hormonal or identified metabolites are associated with measures of insulin sensitivity. Animals: Twenty cats in diabetic remission for a median of 101 days, and 21 healthy matched control cats. Methods: A casual blood glucose measured on admission to the clinic. Following a 24 hour fast, a fasted blood glucose was measured, and blood sample taken for hormone (i.e. insulin, leptin and adiponectin) and untargeted metabolomic (GC-MS and LC-MS) analysis. A simplified IVGGT (1g glucose/kg) was performed 3 hours later. Cats were monitored for diabetes relapse for at least 9 months (270 days). Results: Cats in diabetic remission had significantly higher serum glucose and insulin concentrations, and decreased insulin sensitivity as indicated by an increase in HOMA and decrease in QUICKI and Bennett indices. Leptin was significantly increased, but there was no difference in adiponectin (or body condition score). Several significant correlations were found between insulin sensitivity indices, leptin, and serum metabolites identified as significantly different between remission and control cats. No metabolites were significantly correlated with adiponectin. No predictors of relapse were identified in this study. Conclusion and clinical importance: Insulin resistance, an underlying factor in diabetic cats, persists in diabetic remission. Cats in remission should be managed to avoid further exacerbating insulin resistance.